Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Visible light-triggered disruption of micelles of an amphiphilic block copolymer with BODIPY at the junction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (Chemical Communications, 2015)
A visible light-cleavable polymer is synthesised to overcome the limitations of UV-sensitive polymers. Photocleavable BODIPY functionalized with an ATRP initiator and alkyne was used to obtain an amphiphilic block copolymer by conducting the click reaction and polymerization simultaneously. Micellar assembly of the polymer was disintegrated under visible light irradiation with controlled release of cargo.

Tunable nanocarrier morphologies from glycopolypeptide-based amphiphilic biocompatible star copolymers and their carbohydrate specific intracellular delivery - Pati, Debasis; Das, Soumen; Patil, Naganath G.; Parekh, Nimisha; Anjum, Dalaver H.; Dhaware, Vinita; Ambade, Ashootosh V.; Sen Gupta, Sayam (Biomacromolecules, 2016)
Nanocarriers with carbohydrates on the surface represent a very interesting class of drug-delivery vehicles because carbohydrates are involved in biomolecular recognition events in vivo. We have synthesized biocompatible miktoarm star copolymers comprising glycopolypeptide and poly(e-caprolactone) chains using ring-opening polymerization and ``click chemistry''. The amphiphilic copolymers were self-assembled in water into morphologies such as nanorods, polymersomes, and micelles with carbohydrates displayed on the surface. We demonstrate that the formation of nanostructure could be tuned by chain length of the blocks and was not affected by the type of sugar residue. These nanostructures were characterized in detail using a variety of techniques such as TEM, AFM, cryogenic electron microscopy, spectrally resolved fluorescence imaging, and dye encapsulation techniques. We show that it is possible to sequester both hydrophobic as well as hydrophilic dyes within the nanostructures. Finally, we show that these noncytotoxic mannosylated rods and polymersomes were selectively and efficiently taken up by MDA-MB-231 breast cancer cells, demonstrating their potential as nanocarriers for drug delivery.

Copper and silver nanoparticles stabilized by bistriazole-based dendritic amphiphile micelles for 4-nitrophenol reduction - Patil, Naganath G.; Basutkar, Nitin B.; Ambade, Ashootosh V. (New Journal of Chemistry, 2017)
Copper and silver nanoparticles were fabricated in aqueous solution using micellar assemblies of dendritic amphiphiles containing triazole rings. Dendritic amphiphiles displaying a bistriazole unit between a hydrophobic benzyl ether dendron and two oligo(ethylene glycol) (OEG) chains were synthesized using click chemistry. Micelles were characterized by DLS, TEM, CMC determination, and dye encapsulation. Micellar size was dependent on the dendron backbone structure and OEG chain length. Metal nanoparticles were characterized by TEM and UV-Vis spectroscopy. The Cu NPs had a smaller average particle diameter than the Ag NPs. The micelle-stabilized nanoparticles, at a concentration of 7.5 ppm, were shown to efficiently catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 in aqueous solution without stirring, using up to 1 ppm of substrate. The reaction catalyzed by Cu NPs followed zero order kinetics (k = 3.48 x 10(-3) M s(-1)), while the Ag NP-catalyzed reaction followed pseudo-first order kinetics (k = 1.28 x 10(-3) s(-1)).